Metataxonomic Analysis of Milk Samples From SARS-CoV-2-Positive and SARS-CoV-2-Negative Women - Gómez-Torres, Natalia; Sánchez-García, Laura; Castro, Irma; Arroyo, Rebeca; Cabañas, Fernando; González-Sánchez, Raquel; López-Azorín, Manuela; Moral-Pumarega, M. Teresa; Escuder-Vieco, Diana; Cabañes-Alonso, Esther; Rodríguez, Juan Miguel; Alba, Claudio; et al. (Frontiers in Nutrition, 2022)
Objective: To assess the impact of SARS-CoV-2 viral infection on the metataxonomic profile and its evolution during the first month of lactation. Methods: Milk samples from 37 women with full-term pregnancies and mild SARS-CoV-2 infection and from 63 controls, collected in the first and fifth postpartum weeks, have been analyzed. SARS-CoV-2 RNA was assessed by reverse transcription polymerase chain reaction (RT-PCR) both in cases and controls. After DNA extraction, the V3-V4 hypervariable region of the gene 16S rRNA was amplified and sequenced using the MiSeq system of Illumina. Data were submitted for statistical and bioinformatics analyses after quality control. Results: All the 1st week and 5th week postpartum milk samples were negative for SARS-CoV-2 RNA. Alpha diversity showed no differences between milk samples from the study and control group, and this condition was maintained along the observation time. Analysis of the beta-diversity also indicated that the study and control groups did not show distinct bacterial profiles. Staphyloccus and Streptococcus were the most abundant genera and the only ones that were detected in all the milk samples provided. Disease state (symptomatic or asymptomatic infection) did not affect the metataxonomic profile in breast milk. Conclusions: These results support that in the non-severe SARS-CoV-2 pregnant woman infection the structure of the bacterial population is preserved and does not negatively impact on the human milk microbiota.